POTENSI SUN PROTECTOR FACTOR DAN AKTIVITAS ANTIOKSIDAN SEDIAAN GEL TABIR SURYA ESKTRAK ETANOL DAGING BUAH LABU KUNING (Cucurbita maxima) - Indriastuti, Marlina; Meilani, Utari (Jurnal Insan Farmasi Indonesia, 2024)
Yellow Pumpkin (Cucurbita maxima) is a botanical specimen classified within the Cucurbita genus of the Cucurbitaceae family, commonly utilized as a culinary component by the populace of Indonesia. The chemical constituents identified in pumpkins consist of polyphenols, exhibiting the potential to act as agents safeguarding against photodamage owing to their capacity to absorb ultraviolet radiation. The primary objective of this investigation is to establish the Sun Protector Factor (SPF) of sunscreen gels derived from the ethanol extract of pumpkin flesh, alongside evaluating its antioxidative properties. The research methodology employed for this purpose involves the DPPH free radical scavenging technique utilizing UV-Vis Spectrophotometry for quantitative assessments. The gel formulations were devised in three variations, denoted as formula I (15% concentration), formula II (20% concentration), and formula III (25% concentration), with Carbomer 940 serving as an additional ingredient for the base of the preparation. Results from the study indicate that the formulation yielding the highest SPF value was formula III, registering an SPF value of 7.521. Notably, formula III exhibited the most substantial antioxidative activity, positioning it within the moderate efficacy classification.